Analysis of Game Actions and Performance in Young Soccer Players: A Study Using Sequential Analysis - Sabarit Peñalosa, Alejandro; Morillo-Baro, Juan P.; Reigal-Garrido, Rafael Enrique; Hernández-Mendo, Antonio; Morales-Sánchez, Verónica Odilia (IOAP-MPDI, 2022)
The objective of this research is to analyze the performance of actions in a reduced game situation in a sample of young soccer players. This is a game format in which possession of the ball has to be maintained. The sample consisted of 85 young players aged between 12 and 16 years, observing a total of 58 reduced games and using an analysis instrument called the Game Performance Assessment Instrument (GPAI). The essential data quality analyses are carried out, including the use of correlation indexes, Cohen’s Kappa and the Phi index for intra- and inter-observer reliability. Generalizability and invariance analyses are also performed to estimate the reliability, validity and precision of the numerical structure and its generalizability to other samples or populations with similar distributions. An observational design of nomothetic, punctual and multidimensional types is used, and subsequently, a sequential analysis of the game actions is carried out from the observations. The results show significant relationships between decision-making behaviors (adequate and inadequate) and technical execution behaviors (adequate and inadequate). The findings have highlighted a clear relationship of interdependence between technical execution and decision making. This information is very useful for the design and planning of training oriented to the optimization of sport performance in soccer.
Keywords: Fútbol; Decision making; Technical execution; Sport performance; Soccer